A role for ecology in the evolution of colour variation and sexual dimorphism in Hawaiian damselflies. (21st December 2015) - Cooper, I. A.; Brown, J. M.; Getty, T.
Abstract: Variation in traits that are sexually dimorphic is usually attributed to sexual selection, in part because the influence of ecological differences between sexes can be difficult to identify. Sex‐limited dimorphisms, however, provide an opportunity to test ecological selection disentangled from reproductive differences between the sexes. Here, we test the hypothesis that ecological differences play a role in the evolution of body colour variation within and between sexes in a radiation of endemic Hawaiian damselflies. We analysed 17 Megalagrion damselflies species in a phylogenetic linear regression, including three newly discovered cases of species with female‐limited dimorphism. We find that rapid colour evolution during the radiation has resulted in no phylogenetic signal for most colour and habitat traits. However, a single ecological variable, exposure to solar radiation (as measured by canopy cover) significantly predicts body colour variation within sexes (female‐limited dimorphism), between sexes (sexual dimorphism), and among populations and species. Surprisingly, the degree of sexual dimorphism in body colour is also positively correlated with the degree of habitat differences between sexes. Specifically, redder colouration is associated with more exposure to solar radiation, both within and between species. We discuss potential functions of the pigmentation, including antioxidant properties that would explain the association with light (specifically UV) exposure, and consider alternative mechanisms that may drive these patterns of sexual dimorphism and colour variation.